Effect of Remimazolam versus Propofol on Hemodynamics in Elderly Hypertensive Patients Undergoing Gastroenteroscopy: A Multicenter, Randomized Controlled Clinical Trial - Gu Q; Zeng D; Lin D; Zou J; Sun J; Wang H; Chen S; Zhang H; Xu B; Liu W; Shu J (Drug Design, Development and Therapy)
Qian Gu,1,2,* Deling Zeng,3,* Dayong Lin,4,* Jiang Zou,5,* Jiaxin Sun,1 Huaiming Wang,1 Shiwei Chen,2 Hongwei Zhang,1 Bo Xu,1 Wusong Liu,6 Jinjun Shu1 1Department of Anesthesiology, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 2Department of Anesthesiology, Xichang People’s Hospital, Xichang, People’s Republic of China; 3Health Management Center, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 4Department of Anesthesiology, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 5Department of Anesthesiology, Sichuan Women’s and Children’s Hospital/Women’s and Children’s Hospital, Chengdu Medical College, Chengdu, People’s Republic of China; 6Department of Endoscopy Center, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinjun Shu, Department of Anesthesiology, Sichuan Cancer Hospital, No. 55, Section 4, South Renmin Road, Chengdu, 610041, People’s Republic of China, Email shujinjun@scszlyy.org.cn Wusong Liu, Department of Endoscopy Center, Sichuan Cancer Hospital, No. 55, Section 4, South Renmin Road, Chengdu, 610041, People’s Republic of China, Email liuwusong@scszlyy.org.cnPurpose: This study aimed to compare the effects of remimazolam and propofol on hemodynamics in elderly hypertensive patients undergoing gastroenteroscopy.Methods: In this multicenter, single-blind, randomized clinical trial, 220 hypertensive patients (65– 75 years) scheduled for gastroenteroscopy were randomly assigned to receive either remimazolam (group R, n=110; 0.3 mg/kg induction followed by 0.2– 1 mg/kg/h maintenance) or propofol (group P, n=110; 1.5 mg/kg induction followed by 2– 6 mg/kg/h maintenance), both combined with 0.1 μg/kg sufentanil. Flumazenil or placebo was administered for reversal. Hemodynamics were monitored via Continuous Non-Invasive Arterial Pressure (CNAP). The primary outcomes were hypotension incidence and hemodynamic parameters [mean arterial pressure (MAP), heart rate (HR), cardiac output (CO), and systemic vascular resistance (SVR)]; secondary outcomes included the incidence of other adverse events and recovery time.Results: Group R exhibited significantly lower incidences of hypotension (72.7% vs 37.3%, p < 0.001) and bradycardia (16.4% vs 7.3%, p = 0.037), alongside reduced vasopressor requirements (ephedrine: 3.760 ± 4.133 vs.1.850 ± 3.121, p < 0.001; metaraminol: 0.101 ± 0.208 vs 0.045 ± 0.144, p = 0.012). Both groups exhibited decreased MAP, CO, and SVR at the time point of endoscope entry (T1) compared to 2 minutes before anesthesia induction (T0), while HR reduction was significant only in group P (p < 0.001 vs p = 0.084 in group R). From T1 through 15 minutes post-procedure (T4), group R maintained higher MAP and HR than group P (p < 0.05). Remimazolam was associated with shorter recovery time (p < 0.001), lower rates of respiratory depression (p = 0.002), but higher rates of body movements (p < 0.001) and cough (p = 0.001).Conclusion: Remimazolam provides superior hemodynamic stability and faster recovery compared to propofol in elderly hypertensive patients undergoing gastroenteroscopy, establishing it as a safer sedation option for this vulnerable patient population.Trial Number and Registry Url: Registration number, ChiCTR2400083757; https://www.chictr.org.cn/showproj.html?proj=214795.Keywords: remimazolam, propofol, elderly hypertensive patients, gastroenteroscopy